From isolated tenancy hosted application to multi-tenancy: Toward a systematic migration method for web application - Xuesong Zhang; Beijun Shen; Xucheng Tang; Wei Chen (2010 IEEE International Conference on Software Engineering and Service Sciences, 2010)
Software as a Service (SaaS) attracts small and medium enterprises by its low investment, flexibility and easy to manage. Migrating isolated tenancy hosted web application toward SaaS application can reuse the legacy software assets and cut down the re-development cost and risk. Since multi-tenant is a prime characteristic of SaaS, migrating to multi-tenancy is the prerequisite step of migrating to SaaS. However, it is a hard task complicated by the lack of appropriate migration approaches and tools. In this paper, a systematic method is proposed to migrate and evolve isolated tenancy hosted applications into multi-tenant enabled applications from aspects of data model, access control and tenant management, taking into account both the business needs and technical contents. An experiment has been conducted to tune the approach and evaluate applicability and performance impact of our migration method.